Eine diskursanalytische Kritik der Regulationstheorie - Scherrer, Christoph (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1995)
The article confronts the Marxist variant of the French regulation theory and two recent, conflicting attempts to clarify the role of agency and of the state within the regulation approach, one that upholds claims to objectivity and one that stresses contingency, with the central theoretical insights of Laclau's and Mouffe's discourse analysis. lt argues that if the concept of mutual subversion between the contingent and the necessary is applied to the regulation theory, this theory canavoid the pitfalls of functionalism or of being rejected altogether.